2013
DOI: 10.1155/2013/623789
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Exposure to Nano/Microparticles of Fullerene (C60) Increases Acetylcholinesterase Activity and Lipid Peroxidation in Adult Zebrafish (Danio rerio) Brain

Abstract: Even though technologies involving nano/microparticles have great potential, it is crucial to determine possible toxicity of these technological products before extensive use. Fullerenes C60 are nanomaterials with unique physicochemical and biological properties that are important for the development of many technological applications. The aim of this study was to evaluate the consequences of nonphotoexcited fullerene C60 exposure in brain acetylcholinesterase expression and activity, antioxidant responses, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
2
5
0
1
Order By: Relevance
“…Previous studies have provided evidence that nanoparticles have different effects on AchE activity. For example, metal oxide ones induced an inhibition of this activity (Xia et al, 2013), while fullerene C60 increased it (Dal Forno, 2013). The present findings indicated that a single dose of EUD-NPs (50 mg/kg b.w) given either orally or IP increased AChE activity after different time of exposure in either oral or I.P injected rats.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies have provided evidence that nanoparticles have different effects on AchE activity. For example, metal oxide ones induced an inhibition of this activity (Xia et al, 2013), while fullerene C60 increased it (Dal Forno, 2013). The present findings indicated that a single dose of EUD-NPs (50 mg/kg b.w) given either orally or IP increased AChE activity after different time of exposure in either oral or I.P injected rats.…”
Section: Discussionsupporting
confidence: 58%
“…This was achieved by measuring the oxidative stress parameters in the forebrain, midbrain and hindbrain regions which is recognized as tool to evaluate toxicity mediated by small particles exposure. In addition, the effect of EUD-NPs on the cholinergic activity was estimated by assessing the acetylcholinesterase activity as a biomarker of exposure to neurotoxic compounds (Dal Forno, 2013) as well as the histological changes in the three selected brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there is some concern about the in vivo toxicity of C 60 and other fullerenes. For example, some C 60 derivatives were reported to be highly toxic 52, 53 . Encapsulating these fullerenes may be a good alternative to reduce their in vivo toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, um dos pontos que merece destaque, considerando o cenário analisado até o momento, se refere à juridicização dos riscos. Há evidências científicas de que os riscos poderão ser produzidos a partir de múltiplas fontes, como o risco de inalação e permanência profunda nos pulmões, acarretando danos por atravessar membranas biológicas(CHRISTENSEN, 2015); a comprovação de evidências de que os nanotubos de carbono são potencialmente perigosos em ambientes aquáticos, e que o mecanismo de toxicidade é complexo e insuficientemente compreendido até o momento (BRITTO, 2012); outro estudo mostra possíveis efeitos tóxicos no cérebro (neurotoxicidade) dos peixes Zebrafish (Danio rerio) expostos aos nanotubos de carbono (DAL FORNO et al, 2013). Apesar das promessas substanciais da nanotecnologia, se vislumbram várias áreas de preocupação, que motivam os atuais pedidos por regulação.…”
Section: Nanoprodutos E Nanowaste: Uma Nova "Escala" De Riscos?unclassified